Electronic Justice - Kraft, Martin (2010)
The thesis analyzes the e-Justice projects in the Czech Republic. It describes possibilities of application of individual projects, evaluates the status of their development and their potential future evolution. The thesis also analyzes the economic aspects of selected projects as well as discusses the technological aspects of some technologically advanced projects. On the basis of the analysis of present situation and description of e-Justice issues the contribution of this process for the Czech judiciary system as well as the public government or private persons will be described. The main contribution of this thesis is to objectively evaluate the effects of judiciary digitization for the Czech public administration information systems and related areas.